A COMPARISON OF CATCHABILITY BETWEEN “ARAD” (OTTER BOARD BOAT SEINE) OPERATED WITH AND WITHOUT TURTLE EXCLUDER DEVICES (TEDs) - , Asriyanto; Herry Boesono (JOURNAL OF COASTAL DEVELOPMENT, 2002)
The use of TEDs on the “Arad” (Otter Board Boat Seine Net) has never been done by fishermen from the northern part of the Java Sea in Central Java. In order to introduce this net and also to anticipate the shrimp embargo by World Trade Organization (WTO. TEDs construction used in this study was Hooped TEDs with LxBxD dimension of 60x 40 x 60 cm; width of grids deflector of 5 cm) . This construction made an angle of 45°. Fishing operation with and without TEDs was done 9 times during the day. Shrimp, fish, others and garbage entering the net were measured in terms of body weight and fish body circle was also measured in order to compare the result of each treatment. Both nets (with and without TEDs) contained Shrimp (Metapenaeus sp), Pilot-fish (Selaroides sp), Mackerel (Rastrelliger sp), Hair-tails (Trichiurus sp, Pony-fish(Leiognathus sp), others and garbage. The average catch every hauling for the net with TEDs were : Shrimp 1.17 kg; Fish 1.66 kg; others 0.14 kg and garbage 0.1 kg; whereas the net without TEDs were : Shrimp 1.09 kg; Fish 2.33 kg, others 0.34 kg and garbage 1.31 kg. The average body circle of fish caught by net with TEDs was 4.0-7.4 cm and those caught by net without TEDs was 4.0-8.9 cm. The amount of fish and garbage caught by using each treatment differed very significantly, while the amount of shrimp caught did not.